An Isothermal Molecular Point of Care Testing for African Swine Fever Virus Using Recombinase-Aided Amplification and Lateral Flow Assay Without the Need to Extract Nucleic Acids in Blood - Zhang, Yuhang; Li, Qingmei; Guo, Junqing; Li, Dongliang; Wang, Li; Wang, Xun; Xing, Guangxu; Deng, Ruiguang; Zhang, Gaiping (Frontiers in Cellular and Infection Microbiology, 2021)
African swine fever (ASF) is a highly contagious and usually deadly porcine infectious disease，listed as a notifiable disease by the World Organization for Animal Health (OIE). It has brought huge economic losses worldwide, especially since 2018, the first outbreak in China. As there is still no effective vaccines available to date, diagnosis of ASF is essential for its surveillance and control, especilly in areas far from city with limited resources and poor settings. In this study, an sensitive, specific, rapid and simple molecular point of care testing for African swine fever virus (ASFV) B646L gene in blood samples was established, including treatment of blood samples with simple dillution and boiling for 5 min, isothermal amplification with recombinase-aided amplification (RAA) at 37 oC in a water bath for 10 min, and visual readout with lateral flow assay (LFA) at room temperature for 10-15 min. Without the need to extract viral DNA in blood samples, the intact workflow from sampling to final diagnostic decision can be completed with minimal equipment requirement in 30 min. The detection limit of RAA-LFA forB646L gene-containing plasmid was 10 copies/μL, which was 10 fold more sensitive than OIE-recommended PCR and quantitative PCR. In addition, no positive readout of RAA-LFA was observed in testing classical swine fever virus, porcine reproductive and respiratory syndrome virus, porcine epidemic diarrhea virus, pseudorabies virus and porcine circovirus 2, exhibiting good specificity. Evaluation of clinical blood samples of RAA-LFA showed 100% coincident rate with OIE-recommended PCR, in testing both extracted DNAs and treated bloods. We also found that some components in blood samples greatly inhibited PCR performance, but had little effect on RAA. Inhibitory effect can be eliminated when blood was diluted at least 32-64 fold for direct PCR, while only a 2-4 fold dilution of blood was suitable for direct RAA, indicating RAA is a better choice than PCR when blood is used as detecting sample. Taken together, we established an sensitive, specific, rapid and simple RAA-LFA for ASFV molecular detection without the need to extract viral DNA, providing a good choice for point of care testing of ASF diagnosis .